New emergency and emergency scenarios: intersections with the first Meeting of Nursing Caring in Emergencies of Coren - RS (Research, Society and Development, 2019)
This study aims to discuss the new emergency and emergency scenarios and their intersections with the 1st Meeting of Nursing Caring for Emergencies and Emergencies of COREN - RS. It is a reflective, descriptive and exploratory article that deals with discussions about the occurrence of the aforementioned event. We used the discourse analysis of the event through approximations with the theorizing of Gill (2002). The results permeated the problematizations about the new roles of nursing professionals, focusing on the historical evolution of the profession. We also discussed issues related to integral and resolving nursing education with a focus on approaching the professional with the client. Finally, it was a question of articulating the management models of emergency and emergency units through a critical analysis of the structure, process and results. With this, this study provides the reader with a fertile problematization on the area of urgency and emergency in consonance with the one discussed at the 1st Meeting of Nursing Caring for Emergencies and Emergencies of COREN – RS.